Surgical treatment for metastasis from lymphoepithelioma-like cholangiocarcinoma in the liver: A case report. Issue 19 (May 2018) - Zhang, Jun-Wei; Yang, Hua-Yu; Xu, Yi-Yao; Sang, Xin-Ting; Yu, Shuang-Ni; Huang, Han-Chun; Bian, Jin; Xiong, Jian-Ping; Lu, Xin
Abstract: Rationale: Lymphoepithelioma-like cholangiocarcinoma (LEL-CC) is a rare variant of intrahepatic cholangiocarcinoma (ICC), which is characterized by the better outcome than normal ICC. There is no report about the treatment for the metastasis of the LEL-CC. Here, we describe a rare case of LEL-CC of the liver and report the treatment for metastasis of it. Patient concerns: A 38-year-old woman with a chronic hepatitis B infection was referred to the department of liver surgery in our hospital with a mass in the liver. Diagnoses: A past ultrasound examination had revealed a 28 mm × 16 mm nodular lesion in the right posterior lobe of the liver in May 2013. She had undergone partial resection of the thyroid gland for papillary carcinoma 1 year earlier. Intervention: Suspicious of the metastasis from thyroid cancer, she underwent surgery with liver segmentectomy. The pathologic diagnosis of the lesion was LEL-CC. After surgery, she regularly got checked in our hospital, and in the 6 months after surgery, there was enlargement of lymph node before the inferior vena cava in CT. The doctor did not detect the enlargement of the lymph node until June 2017. The PET-CT was done in June of 2017, which showed the lymph node was hypermetabolic. Outcomes: The patient got her second surgery for lymph node three years after the first surgery, which was proved that the lymph node was metastasis from LEL-CC. The patient was free from recurrence 9 months after surgery. Lessons: We report the first case of surgery for metastasis from LEL-CC in the liver that was diagnosed 3 years after hepatectomy. Our findings suggest that surgery could be an effective way of treating lymph node metastasis of LEL-CC and early PET-CT can help to identify metastasis.